2021
DOI: 10.1101/2021.04.22.440943
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neurexin-3 defines synapse- and sex-dependent diversity of GABAergic inhibition in ventral subiculum

Abstract: Ventral subiculum (vSUB) is integral to the regulation of stress and reward, however, the intrinsic connectivity and synaptic properties of the inhibitory local circuit are poorly understood. Neurexin-3 (Nrxn3) is highly expressed in hippocampal inhibitory neurons, but its function at inhibitory synapses has remained elusive. Using slice electrophysiology, imaging, and single-cell RNA sequencing, we identify multiple roles for Nrxn3 at GABAergic parvalbumin (PV) interneuron synapses made onto vSUB regular spik… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Although vSUB is composed of about 50% RS and 50% BS neurons (Staff et al, 2000; Graves et al, 2012), we found that the majority of NAcMS-projecting neurons in vSUB were RS neurons (70% ± 4) (Figure 1G), which is remarkably consistent with other studies using different retrograde labeling approaches such as retrobeads or cholera toxin B (Kim & Spruston, 2012; Lee et al, 2019). In light of our recent findings that the wiring of vSUB local circuitry is sexually dimorphic (Boxer et al, 2021), we reviewed whether the wiring of the vSUB-NAcMS circuit also exhibits sexual dimorphism. We separated our AAV 2 rg-mRuby experiment by sex but found that equivalent proportions of RS/BS neurons project to NAcMS in male and female mice (%RS: female: 66 ± 4, male: 75 ± 6; U = 2, p = 0.40, Mann-Whitney) (Figure 1G, females: closed circles, males: open circles).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although vSUB is composed of about 50% RS and 50% BS neurons (Staff et al, 2000; Graves et al, 2012), we found that the majority of NAcMS-projecting neurons in vSUB were RS neurons (70% ± 4) (Figure 1G), which is remarkably consistent with other studies using different retrograde labeling approaches such as retrobeads or cholera toxin B (Kim & Spruston, 2012; Lee et al, 2019). In light of our recent findings that the wiring of vSUB local circuitry is sexually dimorphic (Boxer et al, 2021), we reviewed whether the wiring of the vSUB-NAcMS circuit also exhibits sexual dimorphism. We separated our AAV 2 rg-mRuby experiment by sex but found that equivalent proportions of RS/BS neurons project to NAcMS in male and female mice (%RS: female: 66 ± 4, male: 75 ± 6; U = 2, p = 0.40, Mann-Whitney) (Figure 1G, females: closed circles, males: open circles).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the sexually dimorphic organization of vSUB local circuitry (Boxer et al, 2021) prompted us to ask whether the vSUB-specific bias for D2R MSNs was sex-specific. We separated our data by sex but found no sex differences (effect of sex: ns, effect of cell-type: F(1,29) = 6.913, p = 0.014, effect of interaction: ns, Ordinary Two-way ANOVA) (Figure 2C, females: closed circles, males: open circles).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations